From Information to Smart Society Environment, Politics and Economics - Mola, Lapo.; Pennarola, Ferdinando; Za, Stefano; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book presents a collection of research papers focusing on issues emerging from the interaction of information technologies and organizational systems. In particular, the individual contributions examine digital platforms and artifacts currently adopted in both the business world and society at large (people, communities, firms, governments, etc.). The topics covered include: virtual organizations, virtual communities, smart societies, smart cities, ecological sustainability, e-healthcare, e-government, and interactive policy-making (IPM). The book offers a multidisciplinary perspective on a variety of information systems topics. It is also particularly relevant to information systems practitioners such as IS managers, business managers and policy makers. The content is based on a selection of the best papers (original double-blind peer-reviewed contributions) presented at the annual conference of the Italian chapter of AIS, which was held in Milan, Italy in December 2013.
Social Network, On-line Communities and Collaborative Environment -- Smart Cities and Ecological Sustainability -- Countries, Societies and Public Sector.
Keywords: Economics; Information systems; Business planning; Management information systems; Economics/Management Science; Business Information Systems; Organizational Studies, Economic Sociology; Information Systems and Communication Service; Organization/Planning.; Innovation/Technology Management; R & D/Technology Policy